Testicular morphology of the teleost fish Psalidodon xavante (Garutti & Venere, 2009): insights from light and transmission electron microscopy - de Oliveira, Sérgio Marcelino; dos Santos, Fernanda Cristina Alcantara; Taboga, Sebastião Roberto [UNESP]; Mimura, Kallyne Kioko Oliveira (Springer Nature, 2025)
Psalidodon xavante, a teleost fish originally assigned to the genus Astyanax, was recently described and lacks characterization of its testicular histophysiology, spermatogenic processes, and spermatozoa morphology. This study aimed to provide a morphological and ultrastructural description of the testes and spermatozoa of P. xavante. Testes were collected in two distinct seasons and processed for light and transmission electron microscopy. All specimens collected in both periods, regardless of size and weight, were sexually mature. No anatomical differences were observed in gonadal anatomy between both periods collected, indicating no seasonal differentiation in testicular structure. P. xavante displays split spawning, reproducing recurrently throughout the year, as evidenced by the presence of spermatogenic cysts and spermatozoa in both seasons Spermatozoa have a circular/oval head, without acrosome, with an intermediate piece that forms an asymmetric collar around the base of unique flagellum. This study provides the first description of P. xavante testis, demonstrating that the distribution of spermatogonia in seminiferous tubules corresponds to unrestricted type with cystic spermatogenesis. The species exhibits split spawning and possesses mature spermatozoa exclusively within the lumen of seminiferous tubules throughout the year. These findings are essential for the development of tools to understand and preserve this Brazilian cerrado endemic species.Graphical abstract